CAFF CBMP Report No. 11 - Human-Wild Rangifer Systems. Expert Network Monitoring Plan - Arctic Council , Conservation of Arctic Flora and Fauna Working Group (CAFF International Secretariat, 2006)
Human-Wild Rangifer Systems. Expert Network Monitoring Plan. Supporting publication to the CAFF Circumpolar Biodiversity Monitoring Program – Framework Document. By CARMA in cooperation with CAFF